Prediction of soil fertility properties in Southern Brazil via proximal sensing - NACHTIGALL, STEFAN D.; MANCINI, MARCELO; REIS, RENATA A.; ARAÚJO, ELIAS FRANK DE; CARNEIRO, MARCO AURÉLIO C.; CURI, NILTON; SILVA, SÉRGIO HENRIQUE GODINHO (Anais da Academia Brasileira de Ciências, 2025)
Abstract Although proximal sensing coupled with machine learning (ML) algorithms have been successful for characterizing soils, questions remain regarding their effectiveness under varied soil conditions. This study evaluated for the first time the efficiency of a portable X-ray fluorescence spectrometer (pXRF) to predict 17 soil fertility properties in Rio Grande do Sul (RS) state, Brazil, through ML algorithms. A total of 468 surface soil samples were analyzed by pXRF and by conventional (reference) methods. Six algorithms were employed: Projection Pursuit Regression, Partial Least Squares, Random Forest, Support Vector Machine, Extreme Gradient Boosting, and Cubist. Predictions accuracy was assessed using the coefficient of determination (R²), root mean square error, normalized root mean square error, residual prediction deviation (RPD) and Ratio of Performance to Interquartile Distance. Cubist and Random Forest outperformed other algorithms, reaching the following R² values: available/exchangeable Al (R² = 0.70), Ca (0.57), Mg (0.75), Mn (0.84), S (0.60), Cu (0.81), K (0.82), P (0.54), besides P-rem (0.80), H+Al (0.73), and total N (0.52). Predictions for organic carbon and available B, Fe, Na, Zn require further investigations. The pXRF combined with ML algorithms can accelerate decisions for agricultural management in RS state, Brazil, by optimizing soil analysis for improved crop management.